PENGARUH MODEL PEMBELAJARAN TIPE MAKE A MATCH TERHADAP HASIL BELAJAR SISWA KELAS XI MATA PELAJARAN AL-QUR’AN HADITS DI MAN 3 BANYUWANGI - Imam Mashuri; Ainur Rofiq (Jurnal Tarbiyatuna : Kajian Pendidikan Islam, 2021)
The success of a learning process can be seen from student learning outcomes. In the learning process the learning model used will have an influence on students. As in the subject of Al-Qur'an Hadith, today we still easily find learning using conventional methods. So that learning activities will seem ordinary, and bored. This thesis aims to 1) To determine the effect of the Make A Match type learning model on the learning outcomes of class XI students in the Al-Qur'an Hadith subject in MAN 3 Banyuwangi in the 2019/2020 academic year. To determine the extent of the influence of the Make A Match type of learning model on student learning outcomes in the XI class of Al-Qur'an Hadits in MAN 3 Banyuwangi in the 2019/2020 academic year. This research is a quantitative research with a pre-experimental design approach, the type of one group pretest-posttest design. The population in this study were all students of class XI MAN 3 Banyuwangi, totaling 355 students. The sample in this study took a cluster sampling technique, namely class XI MIPA 5 with a total of 39 people. Data collection techniques in this study used observation and tests (pretest and posttest), and documentation. Then for the test analysis using the t test technique. Based on the results of the analysis, it can be concluded that in the class before being treated, the pretest learning outcomes were 71.41. then in the class after being given the treatment obtained posttest learning outcomes of 87.69. From the results of the test analysis, it was found that the data significance value was normally distributed and homogeneous. Furthermore, the hypothesis test was carried out using the t-test in the experimental class, the results of tcount> ttable were 6.745> 2.024, so it could be said that there was an effect of the application of the Make A Match type learning model on the learning outcomes of class XI students in the subject of Al-Qur'an Hadith in MAN. 3 Banyuwangi in the 2019/2020 school year or Ho was rejected and Ha was accepted. The effect of the learning model on student learning outcomes can be seen from the correlation between the pre-test and post-test scores of 0.471. Thus it can be concluded that there is an effect of the Make A Match learning model on the learning outcomes of class XI in the Al-Qur'an Hadith subject in MAN 3 Banyuwangi in the 2019/2020 school year with the moderate category.